White-nose syndrome survivors do not exhibit frequent arousals associated with Pseudogymnoascus destructans infection. Issue 1 (December 2016) - Lilley, Thomas; Johnson, Joseph; Ruokolainen, Lasse; Rogers, Elisabeth; Wilson, Cali; Schell, Spencer; Field, Kenneth; Reeder, DeeAnn
Abstract Background White-nose syndrome (WNS) has devastated bat populations in North America, with millions of bats dead. WNS is associated with physiological changes in hibernating bats, leading to increased arousals from hibernation and premature consumption of fat reserves. However, there is evidence of surviving populations of little brown myotis (Myotis lucifugus ) close to where the fungus was first detected nearly ten years ago. Results We examined the hibernation patterns of a surviving population of little brown myotis and compared them to patterns in populations before the arrival of WNS and populations at the peak of WNS mortality. Despite infection withPseudogymnoascus destructans, the causative fungal agent, the remnant population displayed less frequent arousals from torpor and lower torpid body temperatures than bats that died from WNS during the peak of mortality. The hibernation patterns of the remnant population resembled pre-WNS patterns with some modifications. Conclusions These data show that remnant populations of little brown myotis do not experience the increase in periodic arousals from hibernation typified by bats dying from WNS, despite the presence of the fungal pathogen on their skin. These patterns may reflect the use of colder hibernacula microclimates by WNS survivors, and/or may reflect differences in how these bats respond to the disease.